Recuperación de aluminio del subproducto escoria para optimizar el rendimiento del proceso, generado en la empresa CEDAL S.A. De la ciudad de Latacunga. - Mora Reinozo, Jessica Carmelina (2020)
Cedal S.A. is an Ecuadorian Company, created in 1974 with the purpose of producing and commercializing aluminum products for structural and architectural use. In 1976, it began its productive activities; at present it is the leader in the distribution of aluminum profiles in the country, with more than 40 distributors in Ecuador. Since 1979, they have maintained a solid commercial presence in the related country of Colombia, through its subsidiary VITRAL, which has distributors in Cali and Bogotá, the main cities of this country. Corporación Ecuatoriana de Aluminio, with its production in Latacunga place, linked to the growth and continuous improvement for the quality of its products and involved with the protection of the environment and the reuse of its production waste, sees the need to carry out the recovery of aluminum from the slag by-product to optimize the performance of the production process, thus achieving an efficient use and effective savings. Currently, it has a production capacity of 50 TN per day of aluminum billets, but with an average loss rate by slag of 4% of total production. The present project "Recovery of aluminum from the slag byproduct to optimize the performance of the process, generated in the company Cedal S.A. in Latacunga city, with the purpose of proposing alternative solutions to the use of the waste typical of a process. Through the design of a tilting furnace with refractory walls, the aim is to take advantage of the waste (slag), with an 18% recovery of second melting aluminum, generating an annual profit for the company of $70,888.90 and recovering the invested capital in 4 months. The implementation of the project also improves the management of solid waste thanks to the optimization of processes and the use of innovative machinery.